Principles of macroeconomics - Case, Karl E.; Fair, Ray C. (Upper Saddle River, NJ : Pearson Prentice Hall, 2004)
This student-friendly text takes a hands-on approach to economic theory, issues and politics using a lively writing style which engages the student with clear explanations, easy to understand graphs and relevant examples.
Includes index.
Various multi-media instructional tools are available to supplement the text.
oif 23/04/15,rpm 13/05/15
Loans
Keywords: Macroeconomics; Macroeconomics - principles